2016
DOI: 10.1021/jacs.6b06444
|View full text |Cite
|
Sign up to set email alerts
|

Substituent-Dependent Magnetic Behavior of Discotic Benzo[e][1,2,4]triazinyls

Abstract: Discotic mesogens containing the benzo[e][1,2,4]triazinyl radical as the central unit exhibit a Colh phase below 80 °C. Depending on the substituent at the N(1) position, they show different modes of thermal expansion and magnetic behavior, presumably due to differences in molecular organization. Thus, for 1-phenyl (1a) and 1-PhF-m (1b) derivatives, the Colh phase has positive thermal expansion coefficient κ and antiferromagnetic interactions, while for the 1-(3,4,5-(C12H25X)3C6H2) derivatives 1c (X = O) and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 31 publications
1
58
0
Order By: Relevance
“…The chemistry of the benzotriazinyl radical, known as the Blatter radical, has been developed in the past decade from the viewpoints of synthetic chemistry for the basic skeleton and the transformation of functional groups, as well as a computational study on the π‐electron system . Interesting physicochemical properties, such as spin transitions accompanying a change in molecular packing, liquid‐crystalline behavior, metal coordination,,, intramolecular ferromagnetic interaction in the hetero‐biradical derivative, the formation of a high‐spin molecular assembly, and a zwitterionic singlet state accompanying fluorescence, have been observed in the benzotriazinyl radical family.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of the benzotriazinyl radical, known as the Blatter radical, has been developed in the past decade from the viewpoints of synthetic chemistry for the basic skeleton and the transformation of functional groups, as well as a computational study on the π‐electron system . Interesting physicochemical properties, such as spin transitions accompanying a change in molecular packing, liquid‐crystalline behavior, metal coordination,,, intramolecular ferromagnetic interaction in the hetero‐biradical derivative, the formation of a high‐spin molecular assembly, and a zwitterionic singlet state accompanying fluorescence, have been observed in the benzotriazinyl radical family.…”
Section: Introductionmentioning
confidence: 99%
“…1)1 is an example of a benzotriazinyl radical with remarkable bench-top stability. Although relatively unexplored since the early report by Blatter in 1968, there has been increased recent interest in this radical and derivatives due to their suitability as building blocks for magnetic materials2345678910111213, as polymerization initiators141516 and as ligands in novel radical-metal coordination complexes1718. Related benzotriazines and N-oxide derivatives have seen application in medicinal chemistry, including as anti-cancer drugs, where benzotriazinyl radicals have been proposed as potential DNA-damaging species19202122.…”
mentioning
confidence: 99%
“…Radicals in series 1[n] were obtained in typical yields of 70-90 % using our recently reported protocol [7,9] involving addition of ArLi to benzo[e] [1,2,4]triazine 2 followed by aerial oxidation of the intermediate anion (Scheme 1). The ArLi reagents were generated from the corresponding ArBr 3[n] and t-BuLi.…”
Section: Synthesismentioning
confidence: 99%
“…Recently, we reported [7] discotic materials derived from the exceptionally stable benzo[e] [1,2,4]triazin-4-yl [8] in which the electron spin is delocalized in the π-system of the rigid core. Preliminary experiments indicated that the contact of the π faces and hence the type of spin-spin interactions is controlled by the peripheral substituents.…”
Section: Introductionmentioning
confidence: 99%